Influence of microstructural heterogeneities on capacity to absorb energy of dual-phase steels - Rosenberg, Gejza; Sinaiova, Iveta; Juhar, Lubos (Manufacturing Technology Journal, 2012)
The effect of microstructural banding (or so called segregation bands) on energy absorption capacity of dual-phase steels (DP steels) was examined by product of tensile strength and uniform elongation (TS*UE), as well as by Charpy V-notch impact test. A series of DP steels with different volume fractions of martensite (VFM) was prepared by intercritical annealing at temperatures ranging 740 to 840 °C. It was found that increasing of VFM has an inverse effect on values TS*UE and notch toughness. The results on samples with a notch and pre-cycled crack showed that presence of segregation bands influences capacity of steels to absorb the energy in initial stage as well as in stage of crack propagation.
Keywords: dual phase steel; microstructural banding; energy absorption capacity